Telecommuting Frequency and Preference among Japanese Workers According to Regional Cumulative COVID-19 Incidence: A Cross-Sectional Study. (March 2022) - Baba, Hiroka; Ikegami, Kazunori; Ando, Hajime; Eguchi, Hisashi; Tsuji, Mayumi; Tateishi, Seiichiro; Nagata, Masako; Matsuda, Shinya; Fujino, Yoshihisa; ,
This study aimed to examine the relationship between telecommuting and the regional cumulative COVID-19 incidence. This was a cross-sectional study analyzing 13, 468 office workers. The participant groups, according to the level of cumulative COVID-19 incidence by prefecture, were used as the predictor variable, and telecommuting frequency and preference were used as outcomes. We employed an ordinal logistic regression analysis. In regions with a high cumulative COVID-19 incidence, the proportion of participants who telecommuted more than 2 days per week was 34.7%, which was approximately 20% higher than in other regions. Telecommuting preference was stronger in areas with higher COVID-19 influence. However, in other regions, the proportion of participants who did not want to telecommute was higher than that of those who wanted to telecommute. We found that telecommuting frequency and preference were higher in regions with high cumulative COVID-19 incidence.